Preclinical Testing of Living Tissue-Engineered Heart Valves for Pediatric Patients, Challenges and Opportunities - Movileanu, Ionela; Harpa, Marius; Al Hussein, Hussam; Harceaga, Lucian; Chertes, Alexandru; Al Hussein, Hamida; Lutter, Georg; Puehler, Thomas; Preda, Terezia; Sircuta, Carmen; Cotoi, Ovidiu; Nistor, Dan; et al. (Frontiers in Cardiovascular Medicine, 2021)
Introduction Pediatric patients with cardiac congenital diseases require heart valve implants that can grow with their natural somatic increase in size. Current artificial valves perform poorly in children and cannot grow; thus, living tissue engineered valves capable of sustaining matrix homeostasis could overcome the current drawbacks of artificial prostheses and minimize the need for repeat surgeries. Materials and Methods To prepare living tissue engineered valves, we produced completely acellular ovine pulmonary valves by perfusion. We then collected autologous adipose tissue, isolated stem cells, and differentiated them into fibroblasts and separately into endothelial cells. We seeded the fibroblasts in the cusp interstitium and onto the root adventitia and the endothelial cells inside the lumen, conditioned the living valves in dedicated pulmonary heart valve bioreactors and pursued orthotopic implantation of autologous cell seeded valves with 6 months follow-up. Unseeded valves served as controls. Results Perfusion decellularization yielded acellular pulmonary valves that were stable, non-degradable in vivo, cell friendly and biocompatible, had excellent hemodynamics, were not immunogenic or inflammatory, non-thrombogenic, did not calcify in juvenile sheep and served as substrates for cell repopulation. Autologous adipose derived stem cells were easy to isolate and differentiate into fibroblasts and endothelial-like cells. Cell-seeded valves exhibited preserved viability after progressive bioreactor conditioning and functioned well in vivo for 6 months. At explantation, the implants and anastomoses were intact and the valve root well integrated into host tissues; valve leaflets were unchanged in size, non-fibrotic, supple, and functional. Numerous cells positive for a-smooth muscle cell actin were found mostly in the sinus, base and the fibrosa of the leaflets and most surfaces were covered by endothelial cells. Conclusions Tissue engineered living valves can be generated sing the approach described here. The technology can provide numerous challenges and opportunities, which are discussed in detail in this paper. Overall, we concluded that cell seeding did not negatively affect TEHV performance as they exhibited as good hemodynamic performance as acellular valves in this model. Further understanding of cell fate after implantation and the timeline of repopulation of acellular scaffolds will help us evaluate the translational potential of this technology.